2013
DOI: 10.1158/1535-7163.mct-12-1178
|View full text |Cite
|
Sign up to set email alerts
|

AMG 900, a Small-Molecule Inhibitor of Aurora Kinases, Potentiates the Activity of Microtubule-Targeting Agents in Human Metastatic Breast Cancer Models

Abstract: Breast cancer is the most prevalent malignancy affecting women and ranks second in cancer-related deaths, in which death occurs primarily from metastatic disease. Triple-negative breast cancer (TNBC) is a more aggressive and metastatic subtype of breast cancer that is initially responsive to treatment of microtubuletargeting agents (MTA) such as taxanes. Recently, we reported the characterization of AMG 900, an orally bioavailable, potent, and highly selective pan-Aurora kinase inhibitor that is active in mult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 39 publications
2
50
0
2
Order By: Relevance
“…Caused tumour regression in combination with ixabepilone in triple-negative breast cancer xenografts 304 …”
Section: Figurementioning
confidence: 99%
“…Caused tumour regression in combination with ixabepilone in triple-negative breast cancer xenografts 304 …”
Section: Figurementioning
confidence: 99%
“…Breast cancer ranks as the second cause of cancer death among women (1)(2)(3)(4). Clinical cases have indicated that most of the breast cancer deaths are caused by metastasis (5,6), and as a distinct metastatic pattern, breast cancer cells are more inclined to migrate into lymph nodes, bone marrow, lung, liver and brain (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of NIMA, knockdown of this gene in triple negative tumors induced cell cycle arrest followed by cell death [34]. Similarly, targeting aurora kinases A and B has shown an antitumoral effect in TNBC and these agents were synergistic with MEK inhibitors and agents targeting microtubules [35, 36]. …”
Section: Novel Therapeutic Possibilities In Tnbcmentioning
confidence: 99%